When do photos on products hurt or help consumption? How magical thinking shapes consumer reactions to photo‐integrated products - Wu, Freeman; Samper, Adriana; Morales, Andrea C.; Fitzsimons, Gavan J. (Journal of Consumer Psychology, 2025)
AbstractConsumers and companies frequently integrate products with lifelike photographs of people, animals, and other entities. However, consumer responses to such products are relatively unknown. Drawing on magical thinking and moral psychology, we propose that, due to a photograph's lifelike resemblance to its referent, consumers believe that photo‐integrated products embody the depicted entity's underlying essence. As such, in cases where consumption compromises the product's integrity (e.g., food, disposable goods), people are less likely to consume photo‐integrated products because doing so is perceived as destroying the depicted entity's essence, which elicits moral discomfort. In contrast, when the photographic image remains intact through consumption, as is the case with durable goods (e.g., magnets), people increase consumption of photo‐integrated products relative to products without photo integration, consistent with their popularity in the marketplace. We highlight two strategies to promote more positive outcomes for managers and consumers alike: (1) choose images of entities whose essence destruction is perceived as less immoral, and (2) increase the durability of the product so the depicted entity's essence is preserved through consumption.